Ontological hesitations and performing codes unknown: Haneke, Kiarostami, Binoche and the 'idea' of the screen actor*. Issue 3 (1st September 2016) - Lowe, Victoria
Abstract: This article will look at, to paraphrase Worthen, 'the idea of the screen actor' by thinking through screen acting in relation to Michael Haneke's Code Unknown (2000) and Abbas Kiarostami's Certified Copy (2010). The framing of performance in both these films raises questions around the ethics of spectatorship, particularly in terms of audience identification with character and the implications of this for the politics of representation. Central to this is the labour of the actor, in using their voice and body to elicit identification from the audience. The actress in question is Juliette Binoche, star of both films, whose repertoire and particular range of emotional expressivity would suggest her to be clearly entrenched in an illusionist/realist mode of acting a role. Binoche's performances usually, therefore, invite the audience's strong emotional identification with her characters and I will examine how the films under discussion strategically utilise this performance (rather than star) persona. I will start by examining Code Unknown, firstly locating it within broader traditions of modernist ideas of performance and attempting to outline the crucial part that the 'idea' of screen acting has to play in the ethical relationships created between the film and its spectators. I will then discuss Certified Copy, examining how Kiarostami wrong foots the audience in terms of actor, character and performance in the film. However, I will argue that the ethics of spectatorship with regard to acting on screen are handled somewhat differently by the two directors. Whereas Haneke's treatment of Binoche's performance seems designed to engender an awareness in the spectator of their 'duping' by the performer, Kiarostami moves through this to show an appreciation of the performer as presenting rather than representing a reality.